Altered Functional Performance in Patients with Fibromyalgia - Costa, Isis da Silva; Gamundí, Antoni; Miranda, José G. Vivas; França, Lucas G. Souza; De Santana, Charles Novaes; Montoya, Pedro (Frontiers in Human Neuroscience, 2017)
Fibromyalgia is a common chronic pain condition that exerts a considerable impact on patients’ daily activities and quality of life. Objectives: The main objective of the present study was to evaluate kinematic parameters of gait, functional performance and balance in women with fibromyalgia syndrome. Methods: The study included 26 female patients with fibromyalgia (49.2 ± 8.0 yrs) according to the criteria of the American College of Rheumatology, as well as 16 pain-free women (43.5 ± 8.5 yrs). Gait and balance parameters were extracted from video recordings of participants performing several motor tasks. Non-linear dynamic of body sway time series was also analyzed by computing the Hurst exponent. In addition, functional performance and clinical pain were obtained by using standardized motor tests (Berg´s balance scale, six-minute walking test, timed up and go task, Romberg’s balance test) and self-report questionnaires (Fibromyalgia Impact Questionnaire). Results: Walking speed was significantly diminished (p < .001) in FM patients as compared to pain-free controls, probably due to significant reductions in stride length (p < .001) and cycle frequency (p < .001). Analyses of balance also revealed significant differences between fibromyalgia and pain-free controls on body sway in the medial-lateral and anterior-posterior axes (all ps < .01). Several parameters of gait and balance were significantly associated with high levels of pain, depression, stiffness, anxiety and fatigue in fibromyalgia. Conclusion: Our data revealed that both gait and balance were severely impaired in FM, and that subjective complaints associated with FM could contribute to functional disability in these patients. These findings suggest that optimal rehabilitation and fall prevention in fibromyalgia requires a comprehensive assessment of both psychological responses to pain and physical impairments during postural control and gait.